Mechanisms in ocular hypertension. Issue 5 (May 1979) - Mapstone, R
Abstract : This paper investigates the hypothesis that intermittent partial angle closure is one of the causes of ocular hypertension. 139 eyes from 76 patients with ocular hypertension were provoked with pilocarpine and phenylephrine. Four distinct responses appeared. Firstly, in 39 eyes (from 24 patients, 32%) gonioscopic closure of part or all of the angle appeared. Secondly, in 30 eyes (from 19 patients, 25%) no angle closure occurred but there was a substantial pigment release into the aqueous. Thirdly, in 9 eyes (from 8 patients, 11%) both angle closure and pigment release occurred. Finally, in 61 eyes (from 36 patients, 59%) neither angle closure nor pigment release appeared. (Since the 2 eyes of a patient did not always behave in the same way, for example, 1 eye might develop angle closure and the other not, 1 patient may appear in 2 groups.) From the first group 1 eye from each patient was randomly chosen for iridectomy. A repeat provocative test at least 1 year later produced a significantly different result. It is considered that the evidence obtained in this study supports the hypothesis that intermittent partial angle closure is one of the causes of ocular hypertension.